1999
DOI: 10.1007/s002040050589
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-mediated dichloromethane toxicity and mutagenicity of bacterial and mammalian dichloromethane-active glutathione S-transferases

Abstract: The kinetic properties of bacterial and rat liver glutathione S-transferases (GST) active with dichloromethane (DCM) were compared. The theta class glutathione S-transferase (rGSTTI-1) from rat liver had an affinity for dihalomethanes lower by three orders of magnitude (K(app) > 50 mM) than the bacterial DCM dehalogenase/GST from Methylophilus sp. DM11. Unlike the bacterial DCM dehalogenase, the rat enzyme was unable to support growth of the dehalogenase minus Methylobacterium sp. DM4-2cr mutant with DCM. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…Second, the presence of 1 mM formaldehyde did not affect growth and viability of both the wild type and the polA mutant (Table 1 and data not shown [2 mM formaldehyde led to a prolonged lag phase prior to growth in both wild-type and polA mutant strains]). Finally, constitutive expression from plasmids of the DCM-active GST theta 1-1 from rat in the presence of DCM was more toxic and mutagenic to Methylobacterium and S. enterica serovar Typhimurium TA1535 than that of bacterial DCM dehalogenases, despite a lower conversion rate of DCM to formaldehyde by the rat enzyme under the conditions used (18). In addition, formaldehyde requires a proficient nucleotide excision repair machinery to unfold its mutagenic effects (52), but S. enterica serovar Typhimurium TA1535 is excision repair deficient (26).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Second, the presence of 1 mM formaldehyde did not affect growth and viability of both the wild type and the polA mutant (Table 1 and data not shown [2 mM formaldehyde led to a prolonged lag phase prior to growth in both wild-type and polA mutant strains]). Finally, constitutive expression from plasmids of the DCM-active GST theta 1-1 from rat in the presence of DCM was more toxic and mutagenic to Methylobacterium and S. enterica serovar Typhimurium TA1535 than that of bacterial DCM dehalogenases, despite a lower conversion rate of DCM to formaldehyde by the rat enzyme under the conditions used (18). In addition, formaldehyde requires a proficient nucleotide excision repair machinery to unfold its mutagenic effects (52), but S. enterica serovar Typhimurium TA1535 is excision repair deficient (26).…”
Section: Discussionmentioning
confidence: 90%
“…On the one hand, DCM-converting GSTs from mammals and methylotrophic bacteria have toxic and mutagenic effects in Salmonella enterica serovar Typhimurium (18,44) and Methylobacterium (18). On the other hand, the massive production of hydrochloric acid by cytosolic DCM dehalogenase during growth with DCM suggests that DCM-degrading methylotrophic bacteria may have evolved efficient systems for the maintenance of intracellular pH and for the excretion of chloride ions.…”
mentioning
confidence: 99%
“…To probe the capacity of E. coli cells to cope with the multiple stresses posed by dehalogenation of chlorinated methanes, we have investigated the physiology of E. coli cells expressing DCM dehalogenase\GST of Methylophilus sp. strain DM11 (Bader & Leisinger, 1994 ;Vuilleumier & Leisinger, 1996 ;Gisi et al, 1999). We demonstrate that cells experience no long-term damage from the activity of this enzyme despite transient inhibition of growth during the metabolism of DCM.…”
Section: Introductionmentioning
confidence: 74%
“…S-Chloromethylglutathione has been shown to alkylate DNA (Dechert, 1995) and this is believed to be the basis of the moderately strong mutagenicity in the Salmonella typhimurium Ames tester strain TA1535 expressing mammalian DCM dehalogenase (Thier et al, 1993 ;Gisi et al, 1999). In E. coli and related bacteria, it has been shown that GSH-linked detoxification is intimately associated with potassium efflux systems and the modulation of cytoplasmic pH .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is the dehalogenase activity of theta-class GSTs that makes this class of enzymes so unique [56]. For example, both bacterial and mammalian theta-class GSTs are capable of metabolizing dichloromethane (DCM) to formaldehyde [61]. The oceans are the largest source of organohalogens [62], with representatives from cnidarians including briarane diterpenes [63], bromo-, chloro-and indo-vulones, clavulones and punaglandins (related to mammalian prostaglandins) [64][65][66], and chlorinated sterols [67].…”
Section: Discussionmentioning
confidence: 99%